The Distribution and Physiological Effects of the Myoinhibiting Peptides in the Kissing Bug, Rhodnius Prolixus - Lange, Angela; Alim, Uzma; Vandersmissen, Hans Peter; Mizoguchi, Akira; Vanden Broeck, Jozef; Orchard, Ian (Frontiers in Neuroscience, 2012)
The myoinhibiting peptides (MIPs), also designated as allatostatin-Bs (AST-Bs) or prothoracicostatic peptides (PTSPs) in some insects, are neuropeptides that are characterized by two tryptophan (W) residues at the C-terminal, denoted as the W(X6)Wamide motif. They are believed to be the ancestral ligands for the Drosophila sex peptide (SP) receptor. Physiological functions of MIPs include the inhibition of contraction of insect visceral muscles, in addition to allatostatic and prothoracicostatic activities. The MIP precursor in Rhodnius prolixus encodes MIPs that have an unusual W(X7)Wamide motif. In the present study, MIP-like immunoreactivity was detected within neurons in the central nervous system and within the innervation to the salivary glands, hindgut, and female and male reproductive systems of adult R. prolixus. The effects of peptides with the unusual W(X7)Wamide motif (Rhopr-MIP-4) and with the typical W(X6)Wamide motif (Rhopr-MIP-7) were tested for physiological activity on R. prolixus hindgut contractions. Both peptides reduce the frequency and amplitude of hindgut contractions in a dose-dependent manner. In addition, both peptides activate the Drosophila sex peptide receptor. The MIP/SP receptors are therefore activated by peptides with the unusual W(X7)Wamide motif.